Peningkatan Literasi Reflektif Siswa Sekolah Dasar melalui Proyek P5 tentang Pengungsi Lokal - Caroline, Tristya Febby; Fitri, Naraya; Rachman, Ichsan Fauzi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This article discusses efforts to improve reflective literacy in elementary school students through the P5 project which raises the issue of local refugees. Reflective literacy is not only the ability to read and write but also involves a critical thinking process that later the information can be implemented in personal experience. The method used is a literature approach sourced from various journals, articles, and websites related to improving reflective literacy in elementary school students. The results of the analysis show that contextual approaches, integration of SDG values, and creative activities such as art projects can effectively improve reflective literacy. Solutions such as teacher training and cross-stakeholder collaboration can be supporting strategies, although there are some challenges in their implementation, such as teachers’ limited understanding of students’ interests and needs. Overall, P5 projects focusing on local refugees can serve as an effective tool to teach character to primary school students.